Mathematical modelling and heat transfer observations for Jeffrey nanofluid with applications of extended Fourier theory and temperature dependent thermal conductivity - D.K. Almutairi (Heliyon, 2024)
The suspension of non-Newtonian materials with nanoparticles is important to enhance the thermal phenomenon in various engineering and industrial processes. The versatile research in nanomaterials provide different applications in thermal processes, heat exchangers, thermoelectric devices, HVAC systems, energy processes etc. Following to such novel motivations in mind, current research endorsed the enhancement in heat transfer due to suspension of Jeffrey nanofluid comprising the variable thermal conductivity. The cause of flow is associated to two disks attaining fixed distance. The modified developed relations for Fourier's hypothesis are utilized to model the problem. The flow problem is modeled with appliance of fundamental novel laws. By applying suitable transformations, corresponding differential equations are renovated into dimensionless forms which are solved with applications of analytic homotopic algorithm. The behavior of temperature and velocity due to various parameters is discussed. The numerical calculations have been done for wall shear force and Nusselt number. The results show that the velocity profile boosted due to variation of stretching ratio constant. The enhancement in heat transfer is observed due to Reynolds number. Moreover, the increasing observations for wall shear force in upper and lower disk surfaces are obtained against larger material parameter. The simulated results may find applications in improving heat transfer phenomenon, manufacturing systems, recovery processes, cooling systems, chemical phenomenon, fuel cells etc.